Increasing The Productivity Of Housewives With Jelly Art Training - Eman Sulaiman; Ellin Herlina; Susi Widyastuti (SOCIRCLE : Journal Of Social Community Services, 2022)
Training in pudding jelly art for housewives leads to improved productivity, skill development, and positive economic impact. Through efficient dessert production and increased income, families benefit, and the local economy is positively impacted.